Evaluation of Land Suitability for Durian (Durio zibethinus M.) Plants In Kombi District, Minahasa Regency Based on Geographic Information Systems - Pakasi, Sandra; Siahaan, Anatasya; Najoan, Jemmy; Pioh, Diane; Wantasen, Sofia (EKOTON, 2022)
This study aims to determine the land suitability class and the distribution map of the durian land suitability class in Kombi District by utilizing the Geographic Information System (GIS). This research was conducted using a survey method in the field. In this study, land units were obtained from the results of overlaying land use maps, soil types, and slopes consisting of 52 land units. The results of this study are that the land suitability class for durian plant development in Kombi District is divided into 2 class classifications, namely marginally suitable (S3) with limiting factor for soil texture (r) and nitrogen (n) and not suitable (N) with slope factor (e) The distribution of land suitability class for durian plants in Kombi District is for marginally suitable class (S3) with an area of 5276.71 ha spread over 16 land units and non-suitable class (N) with an area of 2153.44 ha spread over 7 land units. Keywords: Geographic information system (GIS), land suitability evaluation, durian plant Abstrak Penelitian ini bertujuan untuk mengetahui kelas kesesuaian lahan dan peta persebaran kelas kesesuaian lahan durian di Kecamatan Kombi dengan memanfaatkan Sistem Informasi Geografis (SIG). Penelitian ini dilakukan dengan menggunakan metode survei di lapangan. Pada penelitian ini satuan lahan diperoleh dari hasil overlay peta penggunaan lahan, jenis tanah, dan lereng yang terdiri dari 52 satuan lahan. Hasil penelitian ini kelas kesesuaian lahan untuk pengembangan tanaman durian di Kecamatan Kombi terbagi menjadi 2 klasifikasi kelas yaitu sesuai marginal (S3) dengan faktor pembatas tekstur tanah (r) dan nitrogen (n) dan tidak sesuai (N). ) dengan faktor kemiringan (e) Sebaran kelas kesesuaian lahan untuk tanaman durian di Kecamatan Kombi adalah untuk kelas sesuai marginal (S3) dengan luas 5.276,71 ha yang tersebar di 16 satuan lahan dan kelas tidak sesuai (N) dengan luas 2153,44 ha yang tersebar di 7 satuan lahan. Kata kunci: Sistem informasi geografis (SIG), evaluasi kesesuaian lahan, tanaman durian.